The accidental revolutionary : George Whitefield and the creation of America - Mahaffey, Jerome Dean (Baylor University Press, 2011)
Patriots. Founding Fathers. Revolutionaries. For many Americans, the colonial heroes deserve special celebratory reverence. Yet while Washington's leadership, Franklin's writings, and Revere's ride captivate us, the inspiration and influence George Whitefield instilled within the revolutionary spirits of early Americans is regrettably unknown. In this refreshing biography, Jerome Dean Mahaffey deftly moves beyond Whitefield's colonial celebrity to show how his rhetoric and ministry worked for freedom, situating Whitefield alongside the most revolutionary founders. As this Anglica.